2022
DOI: 10.3390/land11020261
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Evolution and the Mechanism behind the Coupling Coordination Relationship between Industrial Integration and Urban Land-Use Efficiency: A Case Study of the Yangtze River Economic Zone in China

Abstract: It is of great significance to explore the dynamic coupling relationship between industrial integration and urban land-use efficiency (ULUE) in order to promote high-quality urban development. This paper presents a system for evaluating industrial integration and ULUE which combines the internal theoretical relationships between the two. Based on this system, this paper analyzes the evolution process and the mechanism behind the coupling coordination relationship between industrial integration and ULUE with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Given the equal importance of farmland transfer and CLGUE, the value is set to 1/2 in this study for every unidentified coefficient. According to the approach of coordination level classification in literatures [ 52 , 53 ], the present study used the uniform distribution function to classify the coordination degree into ten levels ( Table 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Given the equal importance of farmland transfer and CLGUE, the value is set to 1/2 in this study for every unidentified coefficient. According to the approach of coordination level classification in literatures [ 52 , 53 ], the present study used the uniform distribution function to classify the coordination degree into ten levels ( Table 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, combining the above analysis of the temporal properties of the coupling and coordination of the seven urban agglomerations, it can be seen that the spatial radiation effect is strong when the level of coupling and coordination between the systems is in the high-coupling regime. When the level of coupling and coordination between the two systems is low, the spatial radiation effect is also weakened (Ge et al, 2022).…”
Section: Spatial Effect Of Seven Urban Agglomerationsmentioning
confidence: 99%
“…Consistently, It once again confirmed that environmental protection and economic and social development are not absolute conflicts (Tallis et al, 2008), laying a foundation for promoting the sustainable development of the entire watershed. Third, previous studies have focused more on the social and economic activities in the Yangtze River Economic Belt region (Xu et al, 2020;Wang X. et al, 2022;Shi X. et al, 2022;Ge et al, 2022). Few scholars have considered the impact of China's major regional strategies on real life from the perspective of the implementation of the Yangtze River Economic Belt strategy.…”
Section: Contributions and Limitationsmentioning
confidence: 99%